2010
DOI: 10.1258/ijsa.2009.008416
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of an HIV/sexually transmitted disease programme and prevalence of infection among incarcerated men in Jamaica

Abstract: The goal of this study is to describe the establishment of an HIV testing and treatment programme in the Jamaican correctional system and to estimate the prevalence of HIV/sexually transmitted disease (STD) among adult incarcerated men in this country. A demonstration project was implemented by the Jamaican Department of Correctional Services and Ministry of Health in the nation’s largest correctional centre. All inmates were offered HIV and syphilis testing, and a subset was offered chlamydia, gonorrhoea and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
32
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 13 publications
(18 reference statements)
1
32
0
2
Order By: Relevance
“…A total of 2,057 inmates were incarcerated in this institution during the demonstration project period and 1,560 participated in the program. Of these, 1,017 tested for HIV and 24 or 3.3% were found to be HIV-infected (see Andrinopoulos et al 2009 for details of the testing program). This is twice the prevalence rate estimated for the general population (MOH 2006).…”
mentioning
confidence: 99%
“…A total of 2,057 inmates were incarcerated in this institution during the demonstration project period and 1,560 participated in the program. Of these, 1,017 tested for HIV and 24 or 3.3% were found to be HIV-infected (see Andrinopoulos et al 2009 for details of the testing program). This is twice the prevalence rate estimated for the general population (MOH 2006).…”
mentioning
confidence: 99%
“…There have also been occasions when infected inmates having served their terms, were released into the general population [2]; a precursor to HIV epidemic in a generalised HIV setting. Also, due to the confined nature of the Prison community, Inmates engage in risky behaviours ranging from unprotected sex to same sex [3,4] which could increase the rate of HIV transmission among them.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, studies have shown that populations of inmates are vulnerable to HIV, and globally tend to have significantly higher HIV prevalence rate than non-inmate populations [4][5][6][7]. Nevertheless, HIV prevention programmes and data characterizing the epidemic in this group are largely lacking particularly in the developing countries [2,8]. In Ogun state, Nigeria, a literature search yielded no result for HIV related studies conducted specifically among inmates.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations